Pengaruh Ekstrak Kulit Batang Angsana (Pterocarpus indicus Willd.) Terhadap Fertilitas Mencit (Mus musculus L. Swiss Webster) Jantan Secara In Vivo. - Lenggo Geni, Wismi; Sumarmin, Ramadhan; Indriati, Gustina (STKIP PGRI Sumbar, 2014)
Abstract: This study aims to determine the effect of bark extracts (Pterocarpus indicus Willd.) on mice fertility (Mus musculus L. Swiss Webster) males. This study used a CRD (Completely Randomized Design) with the use of test animals (male mice) of3 treatments each treatment consisted of 9 adult mice were given food and drink are adlibitium. K treatment without any extract angsana, treatme nts P1 and P2 is the treatment given angsana extract orally for 36 days with a doseges of 0,1 gr/ b.w and 0,2 gr/ b.w. after granting the extract angsana mating test on each test animal treatment using 1 male mice with female mice 5 to see the number of succesful female mice pregnant. The data analyzed by ANOVA (Analysis Of Varians) and continued with LSD. The results bowed the number of moting female mice 2,8 K. An average P1 of 2,6 and P2 2,4. The number of pregnant female mice were successful average K 2,6, average P1 2.0 and P2 1.2. It can be concluded that the extract of the stem bark of angsana (Pterocarpus indicus Willd.) were given orally for 36 days affects the fertility of mice (Mus musculus L. Swiss Webster) males.